Space matters : exploring spatial theory and practice today - Feireiss, Lukas (Vienna : Ambra V, 2013)
As the subject of earnest discussion, the meaning of space reaches far beyond the horizon of a single discipline. Lukas Feireiss has assembled a collection of international contributions for Space matters, a publication of the space & design strategies study program of the University of Art and Design, Linz, Austria to create an inspiring expansion of the contemporary discourse on space. The publication addresses cultural resarchers and readers in creative professions--architects, artists, curators, scientists and students in all the related fields as well as those members of a broader audience that are interested in the incorporation of space and the pratices with which it is designed in cultural, social and humanities-oriented contexts.
Keywords: Space (Architecture) -- History -- 20th century; Space (Architecture) -- History -- 21st century; Architecture, Modern -- 20th century; Architecture, Modern -- 21st century; City planning